CONFLICT OF REGULATION NORMS FOR HANDLING OF FOREIGN REFUGEES IN SELECTIVE IMMIGRATION POLICIES: CRITICAL LAW STUDIES AND STATE SECURITY APPROACHES - Syahrin, Muhammad Alvi (Nurani, 2020)
The increasing number of asylum seekers and refugees in the territory of Indonesia has caused social disturbances, political security, and even orders in society. The number of their arrivals is not proportional to the number of settlements or placement to the recipient country (Australia). To deal with the problem of asylum seekers and refugees who enter and are in the Indonesian territory, the government issued Presidential Regulation No. 125 of 2016 concerning Handling of Foreign Refugees. This regulation does not only confirm the position of Indonesia pro against refugee humanitarian policies, but also its manufacture which is not in accordance with the legal principles of the establishment of legislation. The legal position of Presidential Regulation No. 125 of 2016 raises disharmony in the legal order (immigration) in Indonesia. Article 7 of Law Number 12 of 2011 has stipulated the order of laws and regulations that form the basis of the enactment of all legal regulations in Indonesia. The provisions of this article are in harmony with the Theory of Norms Hierarchy (Hans Kelsen) which explains that lower norms are valid, sourced and based on higher norms. However, this theory is not enacted in the formation of Presidential Regulation Number 125 of 2016, where in the body the norm is in conflict with the higher legal norms above it. The existence of this regulation has created norm conflicts which have led to the absence of legal certainty. Keywords: Presidential Regulation Number 125 of 2016, Refugees, Immigration